2007
DOI: 10.1177/0093854807300644
|View full text |Cite
|
Sign up to set email alerts
|

Taxometric Analysis of the Psychological Inventory of Criminal Thinking Styles in Incarcerated Offenders and College Students

Abstract: The Psychological Inventory of Criminal Thinking Styles (PICTS) was administered to 427 (204 male and 223 female) incarcerated offenders and 393 (177 male and 216 female) college students in order to assess the latent structure of the PICTS under conditions conducive to the formation of a pseudotaxon. Objective and subjective analyses of 3 different taxometric procedures—mean above minus below a cut (MAMBAC), maximum covariance/maximum eigenvalue (MAXCOV/ MAXEIG), and latent mode (L-Mode) factor analysis—in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Contrary to our expectations, criminal cognitions were signifi cantly higher among civil psychiatric patients than among male prison inmates. Specifi cally, the PICTS scales of mollifi cation, cutoff, entitlement, power orientation and sentimentality were all signifi cantly higher in this psychiatric sample compared with non-mentally ill male inmates (Walters and McCoy, 2007). This is particularly noteworthy because our sample of psychiatric patients was signifi cantly older than the inmate sample.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Contrary to our expectations, criminal cognitions were signifi cantly higher among civil psychiatric patients than among male prison inmates. Specifi cally, the PICTS scales of mollifi cation, cutoff, entitlement, power orientation and sentimentality were all signifi cantly higher in this psychiatric sample compared with non-mentally ill male inmates (Walters and McCoy, 2007). This is particularly noteworthy because our sample of psychiatric patients was signifi cantly older than the inmate sample.…”
Section: Discussionmentioning
confidence: 72%
“…underage drinking) or denied any criminal behaviour. In a subsequent analysis, Walters and McCoy (2007) found that several PICTS thinking styles scales were actually higher in the male college sample as compared with the male offender sample, although this effect was attributed to the younger age of the college sample. When age was statistically controlled, scores in the offender sample were higher.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…As the name suggests, this is a cognitive style or belief system that contributes to criminal behavior (Walters, 2006). Although criminogenic thinking has historically been discussed mainly in regard to criminal offenders, criminogenic thinking occurs on a continuum and everyone engages in some level of criminogenic thinking, which can perpetuate noncriminal maladaptive and irresponsible behavior (Walters & McCoy, 2007). Researchers in this area have provided different conceptualizations of what constitutes criminogenic thinking.…”
mentioning
confidence: 99%